[bmim]PF6/KOH: A Recyclable Catalytic System for an Azide–Arylacetaldehyde [3 + 2] Cycloaddition. (November 2017) - Jiang, Yuqin; Wu, Kai; Tan, Xuxia; Zhang, Dandan; Dong, Wenpei; Li, Wei; Xu, Guiqing; Zhang, Weiwei
A fast and green protocol for the synthesis of 1, 4-disubstituted 1, 2, 3-triazoles from azides and arylacetaldehydes at room temperature was developed using [bmim]PF6 /KOH as the reaction medium. It was found that the in situ -generated carbene from [bmim]PF6 /KOH acted as the catalyst. In the absence of a transition-metal catalyst and organic solvent, this azide–arylacetaldehyde [3 + 2] cycloaddition proceeds efficiently, with high levels of regioselectivity, broad range of substrates, excellent yields and simple operation under mild conditions.